Applying whole exome sequencing in a consanguineous population with autism spectrum disorder. (4th March 2023) - Al-Mamari, Watfa; Idris, Ahmed B.; Al-Thihli, Khalid; Abdulrahim, Reem; Jalees, Saquib; Al-Jabri, Muna; Gabr, Ahlam; Al Murshedi, Fathiya; Al Kindy, Adila; Al-Hadabi, Intisar; Bruwer, Zandrè; Islam, M. Mazharul; et al.
Abstract : This study aimed to systematically assess the impact of clinical and demographic variables on the diagnostic yield of Whole Exome Sequencing (WES) when applied to children with Autism Spectrum Disorder (ASD) from a consanguineous population. Ninety-seven children were included in the analysis, 63% were male and 37% were females. 77.3% had a suspected syndromic aetiology of which 68% had co-existent central nervous system (CNS) clinical features, while 69% had other systems involved. The diagnostic yield of WES in our cohort with ASD was 34%. Children with seizures were more likely to have positive WES results (46% vs. 31%, p  = 0.042). Probands with suspected syndromic ASD aetiology showed no significant differential impact on the diagnostic yield of WES.